Precious Moments : Storybook Bible - Butcher Sam; Sam Butcher (United States Thomas Nelson, 2003)
It focuses on themes of God$1 (Bs love, faith, and obedience, featuring stories like Noah$1 (Bs Ark, David and Goliath, and the life of Jesus.s
English
Keywords: children's non-fiction literature